ISOLATION AND IDENTIFICATION OF FLAVONOIDS FROM Sesamum indicum - Priyanka Sharma; Renu Sarin (Indonesian Journal of Pharmacy, 2012)
Natural  substances  have  long  served  as  sources  of therapeutic  drugs.  Many  substances  have  been  derived  from traditional medicines. The plants are rich in secondary metabolites. The medicinal properties of these plants have been attributed to the biochemicals present in the plant materials. In addition to their role in  human  and  animal  nutrition,  knowledge  of  micronutrients  and phytochemical  composition  is  fundamental  to  the  understanding  of modes and mechanisms of action of medicinal plants in general. In the  present  investigation,  quercetin  and  kaempferol  have  been isolated  and  identified  from  stem,  leaves  and  unorganized  cultures of  Sesamum  indicum  and  maintained  by  frequent  subculturings  on Murashige  and  Skoog’s  medium  (1962)  supplemented  with NAA+BAP(5.0+0.5mg/L).  The study showed that maximum content of quercetin and kaempferol was observed in 6 weeks old calli and minimum  in  stem  of  S.  indicum.  The  structure  of  the  isolated compound  was  established  on  the  basis  of  physical,  chemical  test and spectroscopic evidences.Key words: Flavonoids,  quercetin,  kaempferol, Sesamum indicum